The Effectiveness of Hope-Therapy on the Enhancement of Happiness in Elderly - Elham Parvaneh (روانشناسی پیری, 2015)
TOday health researchers to study the subjects in clinical and non-clinical environments, consider not only health indicators,but to examine the broader factors such as happiness. The purpose of this study was to investigate the effectiveness of the therapeutic hope in increase the happiness of the elderly. Semi-experimental research design was a pretest-posttest control group. The statistical population of the study, all elderly living innursing homesin Kermanshah, Then Farzanegan's nursing hom eof Kermanshah was selected byavailable sampling method and Considering the inclusion criteria, 24 elderly people with an average age of 64 years, randomly divided into two experimental and control groups. The experimental group received 8 sessions of The Hope-Therapy. The results covariance analysis showed that Hope-Therapy in the elderly has been effective in increasing happiness.Based approach to therapeutic intervention can to be an effective intervention to increase the happiness elderly used.